Surgical and Patient Risk Factors for Severe Arterial Line Complications in Adults. (March 2016) - Nuttall, Gregory; Burckhardt, Jennifer; Hadley, Anita; Kane, Sarah; Kor, Daryl; Marienau, Mary Shirk; Schroeder, Darrell R.; Handlogten, Kathryn; Wilson, Gregory; Oliver, William C.
Abstract : Background: Prior research has provided inconsistent data regarding the risk factors associated with complications from arterial cannulation. The goal of this study was to clearly define the incidence and risks factors associated with arterial cannulation complications. Methods: After obtaining institutional review board approval, all patients requiring arterial line placement with documentation were included in this retrospective study between January 1, 2006, and December 31, 2012. Leveraging two robust data warehouses, the Perioperative DataMart and the Mayo Clinic Life Silences System, the authors cross-matched arterial line cannulation with a documented vascular consult, neurologic consult, infection, or return to surgery within 30 days in order to identify the initial patient population. Results: A total of 62, 626 arterial lines were placed in 57, 787 patients, and 90.1% of the catheters placed were 20-gauge catheters. The radial artery was cannulated in 94.5% of patients. A total of 21 patients were identified as having experienced vascular complications or nerve injuries, resulting in a complication rate of 3.4 per 10, 000 (95% CI, 2.1 to 5.1). Cardiac surgery had the largest number of catheters placed (n = 15, 419) with 12 complications (complication rate = 7.8 per 10, 000; 95% CI, 4.0 to 13.6). The rate of complications differed significantly ( P < 0.001) across the three most common catheter sizes (2.7 per 10, 000 [95% CI, 1.5 to 4.4] for 20 gauge, 17.2 per 10, 000 [95% CI, 4.7 to 43.9] for 18 gauge, and 9.4 per 10, 000 [95% CI, 1.1 to 34.1] for 5 French). Conclusion: In a large retrospective study, the authors document a very low rate of complications with arterial line placement.